The Emerging Role of Sonoelastography in Pregnancy: Applications in Assessing Maternal and Fetal Health - Abdulrahman M. Alfuraih (Diagnostics)
Sonoelastography, a novel ultrasound-based technique, is emerging as a valuable tool in prenatal diagnostics by quantifying tissue elasticity and stiffness in vivo. This narrative review explores the application of sonoelastography in assessing maternal and fetal health, with a focus on cervical, placental, pelvic floor, and fetal tissue evaluations. In the cervix, sonoelastography aids in predicting preterm birth and assessing labor induction success. For the placenta, it provides insights into conditions like preeclampsia and intrauterine growth restriction through elasticity measurements. Assessing fetal tissues, including the lungs, liver, and brain, sonoelastography offers a non-invasive method for evaluating organ maturity and detecting developmental anomalies. Additionally, pelvic floor assessments enable better management of childbirth-related injuries and postpartum recovery. While current studies support its safety when used within established limits, further research is necessary to confirm long-term effects. Future advancements include refining protocols, integrating machine learning, and combining sonoelastography with other diagnostic methods to enhance its predictive power. Sonoelastography holds promise as an impactful adjunct to conventional ultrasound, providing quantitative insights that can improve maternal and fetal outcomes in prenatal care.